Islamic Education and Environmental Ethics: Integrating Eco-Theology into Sustainable Learning Practices - Khalid Abdullah Al Muzaini; Mohammad Ahmad Bani Amer; Markhabat Bolat; Maryam Rashid Saleh Al Tamimi; Muneera Mohammed Al Dossary (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2024)
This study aims to develop an Islamic educational framework that integrates environmental ethics with sustainable learning practices through the perspective of Islamic eco-theology. A qualitative library research approach was employed by examining scholarly literature on Islamic environmental ethics, sustainability education, ecological theology, and curriculum development. Data were analyzed using thematic content analysis to identify the relationship between Qur'anic environmental principles and contemporary educational practices. The findings indicate that Islamic education possesses a comprehensive ethical foundation for promoting environmental stewardship through the concepts of khalīfah (vicegerency), amānah (trust), mīzān (balance), and iṣlāḥ (environmental restoration). Integrating these principles into educational practices encourages students to develop ecological awareness, environmental responsibility, and sustainable lifestyles while strengthening their spiritual commitment. The proposed framework combines Islamic environmental ethics with sustainability-oriented pedagogy to support holistic student development. The novelty of this study lies in constructing an integrated eco-theological educational framework that bridges Islamic teachings with contemporary sustainability education